A Bi-cultural Townscape: Wellington in the 1940s - Schrader, Ben (Architectural History Aotearoa, 2014)
Included in the baggage the first settlers brought to Wellington were prefabricated cottages built in London. According to their designer and maker – Manning of Holborn – these "flat-pack" homes could be erected in only a few hours. All that was needed was a wrench to put them together. For settlers, the advantage of the prefabricated dwellings was the chance to create an "instant home." Constructed together they would create an immediate and modern British–like townscape in an exotic land. Why then did so many settlers quickly abandon their prefabricated dwellings for raupō structures built by Māori? How come raupō dwellings proliferated in Wellington and not in Auckland? And why were measures were put in place to restrict their construction from 1844? This paper focuses on the early settlement of Wellington when the town had a hybrid-built environment – comprising both European and Māori-designed structures – and Māori and Pākehā lived side by side. These attributes set Wellington apart from other towns in New Zealand and similar settler societies. So why was this unique bi-cultural townscape subsumed by an overtly European one by 1850?